The Contribution of Physical Fitness, Infrastructures and Learning Motivation to the Learning Result of Physical, Sport and Health Education - Arri Kusnadi; Bafirman HB; Syahrial Bakhtiar (Fakultas Ilmu Pendidikan UNP)
This research is conducted based on the problems of Grade VIII students in Junior High School 1 Tembilahan, Kabupaten Indragiri Hilir where the learning result of the students is low, physical fitness, and the Physical, Sport and Health Education’s infrastructures and motivation which less than good. The purpose of this research is to discover the significant contribution between physical fitness, infrastructures and learning motivation altogether to the learning result of Physical, Sport and Health Education of Grade VIII students in Junior High School 1 Tembilahan, Kabupaten Indragiri Hilir. This research uses a quantitative approach, namely correlation research (Correlational Research). The study population is 382 students of grade VIII SMP Negeri 1 Tembilahan. The sample of this research is 80 students who obtained by using simple random sampling. The data were collected by conducting tests on samples. Physical fitness data obtained by TKJI, learning motivation data obtained by questionnaire dispersion and infrastructure facilities obtained questionnaire and observation. While the data of the learning result of Physical, Sport and Health Education. To calculate the amount of contribution used Formula Index Determinasi, that is r2 x 100%. According to the analysis 1) The physical fitness is related to the learning result of Physical, Sport and Health Educationrxy=0.448, and contributes by 20%. 2) The Infrastructures is related to the learning result of Physical, Sport and Health Education rxy=0.325, and contributes by 10.5%. 3) the learning motivation is related to the learning result of Physical, Sport and Health Education rxy=0.353, and contributes by 12.4%. 4) The physical fitness, infrastructures, and learning motivation is related to the learning result of Physical, Sport and Health Education rxy=0.574, and contributes, altogether, by 32.95 to the learning result of Physical, Sport and Health Education.